1995
DOI: 10.1177/088740349500700301
|View full text |Cite
|
Sign up to set email alerts
|

A Study of State Certification Exam Results for Florida Police and Correctional Recruits in Relation to Grade-Level Equivalency

Abstract: Although the high school diploma is almost universally required for criminal justice employment, it has become widely discredited as no longer being a meaningful indicator of reading, writing, or computational abilities. This study examines one state's response to this discrepancy through minimum competency testing for police and correctional recruits undergoing entry-level training. Multiple regression techniques are used to determine: (1) to what extent demographic variables are predictive of recruit's basic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It is no secret that the American Medical Association (AMA) certifies doctors, and the American Board of Medical Specialties (ABMS) assists 24 approved medical specialty boards in the development and use of standards in the ongoing evaluation and certification of physicians (http://www.abms.org/). Many people know that accountants are often certified accountants (see Macdonald, 1984, for a history of professionalizing accountants), but consider the following list of occupations that claim and now require certification for their "professionals": athletic trainers (Massie & Whitman, 2008); the gamut of engineers including wireless communication (Frantz 2008); personal trainers (Robinson, Graham, & Bauer, 2006); child welfare service staff (Birmingham, Berry, & Bussey, 1996); law enforcement, police, and corrections (Stinchcomb and Clinton 1995); emergency services and technicians (Casey, Wholey, & Moscovice, 2008); health care staffing services and now home health care (Gingerich, 2007); nursing with ever-more increasing specialization within the field (see Baird, 2007). Even ice hockey officials are certified!…”
Section: Is Certification Of Procurement Practitioners Needed?mentioning
confidence: 99%
“…It is no secret that the American Medical Association (AMA) certifies doctors, and the American Board of Medical Specialties (ABMS) assists 24 approved medical specialty boards in the development and use of standards in the ongoing evaluation and certification of physicians (http://www.abms.org/). Many people know that accountants are often certified accountants (see Macdonald, 1984, for a history of professionalizing accountants), but consider the following list of occupations that claim and now require certification for their "professionals": athletic trainers (Massie & Whitman, 2008); the gamut of engineers including wireless communication (Frantz 2008); personal trainers (Robinson, Graham, & Bauer, 2006); child welfare service staff (Birmingham, Berry, & Bussey, 1996); law enforcement, police, and corrections (Stinchcomb and Clinton 1995); emergency services and technicians (Casey, Wholey, & Moscovice, 2008); health care staffing services and now home health care (Gingerich, 2007); nursing with ever-more increasing specialization within the field (see Baird, 2007). Even ice hockey officials are certified!…”
Section: Is Certification Of Procurement Practitioners Needed?mentioning
confidence: 99%
“…A prevalent assertion indicated that racial minority applicants were likely to score lower on a variety of recruitment-related tests due to their limited educational accomplishment. For example, Stinchcomb and Terry (1995) indicated that Caucasian applicants, rather than ethnic minority applicants, were likely to score higher on the written tests (e.g., math or reading), which might simply reflect the applicants' educational experience. Accordingly, the primary concern is that an adverse impact may be imposed on racial minority applicants if the police department adopts a 4year college degree as the minimum educational requirement in the police selection process.…”
Section: Racial Issues In the Police Selection Processmentioning
confidence: 99%